ISLAM, PLURALITAS AGAMA, DAN PEMBENTUKAN MASYARAKAT MADANI DI INDONESIA - Lukmanul Hakim (Harmoni, 2012)
Plurality is inevitable in Indonesia. Plurality of religions is an asset of Indonesia. Plurality covers various aspects of social and religious life for both are related and inseparable . The socio-religious life has had many variety and is not always associated with positive values based upon the reality in the society. Friction and conflicts also occasionally occur, both among religious followers, and also fellow believers which commonly ends with disagreements. In order to result in positive impacts upon plurality or diversity, a good conflict management is needed. In relation to the establishment of civil society in Indonesia, good conflict management will provide a wide range of sphere for each individual to develop their creativeness and ideas for a better social and religious life.